Microsoft Office 2013 : introductory - Vermaat, Misty E., author; Freund, Steven M. (Boston, MA : Cengage Learning)
Introduction to Technology -- Office 2013 and Windows 8: Essential Concepts and Skills -- Office 365 Essentials -- Microsoft Word 2013 --Microsoft PowerPoint 2013 -- Microsoft Excel 2013 -- Microsoft Access 2013 -- Microsoft Outlook 2013 -- Capstone Projects -- Index -- Quick Reference -- Important Notes for Windows 7 Users.